Highly efficient microstrip patch antenna for wireless gigabit alliance applications - Soumen Barua; Abu Zafar Md. Imran; Md. Emdadul Hoque Bhuiyan; Subrata Barua; Syed Zahidur Rashid; Abdul Gafur; Md. Razu Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A wireless gigabit alliance (WiGig) is widely known for higher bandwidth which operates at 60GHz unlicensed spectrum for super-fast data speed over short distances for millimeter-wave band application. This study offers an efficient, compact microstrip patch antenna for WiGig with a lesser return loss -50.45 dB (60 GHz). The gain and directivity of the proposed antenna are 13.01 dB and 13.42 dBi. It provides higher efficiency of around 91%. The proposed antenna also covers another mm-wave band that is at 95 GHz. The U.S. military uses electromagnetic radiation of 95 GHz as a non-lethal weapon. So, the anticipated antenna can be used for a miniaturized active denial system. The proposed antenna has a good gain, directivity, and efficiency for the multigigabits/s data rate. The aforesaid properties imply that it can be used for wireless personal area networks (WPAN) and wireless local area network (WLAN) and fifth-generation (5G) applications too.